2019
DOI: 10.3847/1538-4357/ab3e39
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Density and Temperature Profiles Calculated by Forward Modeling EUV Emission Observed by SDO/AIA

Abstract: We present a model for the intensity of optically thin EUV emission for a plasma atmosphere. We apply our model to the solar corona as observed using the six optically thin EUV channels of the SDO/AIA instrument. The emissivity of the plasma is calculated from the density and temperature using CHIANTI tables and the intensity is then determined by integration along the line of sight. We consider several different profiles for the radial density and temperature profiles, each of which are constrained by the obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…They suggested that the density derived from the cooler lines (Fe VIII) probes the cool coronal hole plasma and the hotter lines show a contribution from quiet-Sun plasma. This also agrees with the results by Pascoe, Smyrli, and Van Doorsselaere (2019) that estimated coronal hole electron densities are around ≈ 10 8 cm −3 . Figure 8 shows that the density decreases as a function of the distance from the coronal hole boundary up to d ≈ 20 .…”
Section: Discussionsupporting
confidence: 93%
“…They suggested that the density derived from the cooler lines (Fe VIII) probes the cool coronal hole plasma and the hotter lines show a contribution from quiet-Sun plasma. This also agrees with the results by Pascoe, Smyrli, and Van Doorsselaere (2019) that estimated coronal hole electron densities are around ≈ 10 8 cm −3 . Figure 8 shows that the density decreases as a function of the distance from the coronal hole boundary up to d ≈ 20 .…”
Section: Discussionsupporting
confidence: 93%
“…The extent to which this is due to observational issues, rather than genuine evolution of the loops, remains to be determined. That study was also based on DEM analysis which is known to produce overly broad spectra (e.g., Van Doorsselaere et al, 2018;Pascoe et al, 2019b) which may conceal the signatures of KHI.…”
Section: Discussionmentioning
confidence: 99%
“…This broadness can be overestimated by DEM inversions (e.g. Van Doorsselaere et al 2018;Pascoe et al 2019b). Changes in loop intensity can also be associated with radiative cooling, with typical cooling times being tens of minutes (e.g.…”
Section: Analysis Of Kink Oscillationsmentioning
confidence: 99%